Analysis of Constructive Learning Models in Forming Religious Characters of Early Childhood - Mulyati, Mulyati; Sumadi, Tjipto; Yetti, Elindra (Universitas Negeri Semarang, 2020)
The purpose of this study is to provide an overview of the development of learning models that can stimulate students to interpret every learning activity in shaping the character of early childhood. The research method is a qualitative method in which the researcher captures the phenomenon of the development of religious and moral values of early childhood is only limited to habituation and the discovery of data that the teacher does not compile a special program of character development in learning. The study was conducted in DKI Jakarta (Jakarta Capital Special Region) with 60 samples consisting of University students Open PAUD (Early Childhood Education) majors who are PAUD teachers in DKI Jakarta. Data collection techniques from interviews, observation and questionnaire distribution and also documentation. The results of the study stated that a constructive learning model is needed that is able to give meaning to the learning process in character development.